Transcriptomic Adaptation of Legionella pneumophila to Transient Heat Shock - Liang, Jeffrey; Faucher, Sebastien P. (Frontiers in Water, 2022)
A natural inhabitant of freshwater microbial ecology, Legionella pneumophila is an opportunistically pathogenic bacteria that has found a niche in hot water distribution systems (HWDS) where it challenges hospitals with the spread of nosocomial infection. Superheat-and-flush is a high-temperature pasteurization which can be temporarily effective, but systems often test positive for contamination soon after pasteurization. Because of the centrality of pasteurization in HWDS sanitation schemes, an understanding of the L. pneumophila intrinsic heat shock response may help improve the strategies used to counter its proliferation and ability to trigger nosocomial outbreaks. We tested a group of strains to assess differences in heat shock tolerance between clinical, laboratory, and environmental strains of different origin. The transcriptome of a model Philadelphia-1 L. pneumophila strain in response to heat shock was determined using microarray as an exploratory analysis of the heat shock response: 401 genes were induced, including genes involved in determining protein fate and ribosome biosynthesis while 43 genes were downregulated. Mutants of 3 individual genes were tested to find their direct effects on heat shock tolerance. Deletions of dksA or rpoS, genes involved in the regulation of life cycle switching and important for surviving long-term nutrient deprivation in freshwater lowered heat shock tolerance, suggesting an overlap in the pathways required to tolerate these stressors. Surprisingly, the deletion of htpG, the 90-kilodalton heat shock protein, was found to increase the ability to survive under transient heat shock. Taken altogether, our results show that L. pneumophila exhibits most components of the conserved bacterial heat shock response. Based on this exploratory transcriptomic study, we have provided data that can act as a platform for the research of L. pneumophila's survival to pasteurization in hot water systems.